2006
DOI: 10.1631/jzus.2006.b0830
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the tumor suppressor Krüppel-like factor 6 (KLF6) by mutation or decreased expression in hepatocellular carcinomas

Abstract: Background and aim: The Krüppel-like transcription factor KLF6 is a novel tumor-suppressor gene. It was inactivated in human prostate cancer and other tumors tissue, as the result of frequent mutation and loss of heterozygosity (LOH). However, there is no data reporting the levels of KLF6 both mRNA and protein in hepatocellular carcinomas (HCCs). We therefore detected mutations and expression of KLF6 in HCC tissues and further observed the effect of it on cell growth in HCC cell lines. Methods: We analyzed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…These findings complement our original report describing frequent loss and somatic mutation in primary HCC tumor samples (Kremer-Tal et al, 2004). In a separate study, somatic mutations were identified in 8.7% of patient samples (Pan et al, 2006). In addition, LOH was reported in 6.8% of tumors with no mutation or promoter methylation in a Korean cohort of HCCs (Song et al, 2006).…”
supporting
confidence: 85%
“…These findings complement our original report describing frequent loss and somatic mutation in primary HCC tumor samples (Kremer-Tal et al, 2004). In a separate study, somatic mutations were identified in 8.7% of patient samples (Pan et al, 2006). In addition, LOH was reported in 6.8% of tumors with no mutation or promoter methylation in a Korean cohort of HCCs (Song et al, 2006).…”
supporting
confidence: 85%
“…Generally, the inactivation of a tumor suppressor associated with loss of expression results from genetic or epigenetic alterations, such as mutation, allelic loss or hypermethylation of the promoter region of the genes. Recently, genetic alterations of KLF6 gene have been identified in several human cancers, including hepatocellular carcinoma, prostate cancer, head and neck squamous cell carcinoma, gastric and colon cancer [11,12,[23][24][25]. Interestingly, the KLF6 mRNA was also frequently down-regulated in non-small-cell lung cancer, glioblastoma and colon cancer cell lines [5,6,10,13,26].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the other studies, they only analyzed exon 2. None of the other studies included methods to [10][11][12][13] (ranging between 0 and 15%) and colorectal carcinoma [14][15][16][17][18] (ranging between 0 and 44%). Similar to prostate cancer, the first studies conducted on these other tumors indicated a high frequency of mutation, but this was not reproduced in subsequent reports.…”
Section: Discussionmentioning
confidence: 99%
“…9 The reported frequency of KLF6 mutations in different types of human cancer varies in the different published studies. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In prostate cancer, four studies have analyzed the frequency of KLF6 mutations. 6,[30][31][32] In the first published study, Narla et al 6 showed a very high frequency, 55%, whereas in the following study, Chen et al 30 obtained a lower frequency, around 15%.…”
mentioning
confidence: 99%